Evaluating the Professional Competence of Iranian Midwives in Childbearing Counseling: A Comprehensive Assessment - Rajabi, Mitra; Farid, Malihe; Esmaelzadeh Saeieh, Sara; Najafi Sharjabad, Fateme; Olfati, Forouzan; Shahmirzad, Nilufar; Akbari Kamrani, Mahnaz (Advances in Nursing & Midwifery, 2024)
Introduction: Midwives play a crucial role in promoting maternal and neonatal health, making it essential to evaluate their effectiveness in childbirth counseling. This study aims to assess the competency of midwives in providing childbirth counseling at comprehensive health centers in Qazvin city, Iran. Methods: A cross-sectional study was conducted in 2022 utilizing a census sampling method, encompassing all 88 midwives in Qazvin city, Iran. The study utilized a demographic questionnaire and Midwifery Professional Competency Standard Tool for Childbirth Counseling, consisting of 46 questions across five areas: professional/ethical counseling, comprehensive care, interpersonal relations, organization and coordination, and personal/professional development. Data were analyzed using SPSS v23 software. Results: The mean age of participants was 37.420±7.729 years. The competency scores ranged from 137 to 230, with a mean of 200.750±13.461. The results revealed that 88.7% of the participants were accountable for their professional performance in professional-ethical competency. The mean scores for midwifery professional competencies in ethical/professional, comprehensive care, interpersonal relationships, organization-coordination, and personal/professional development were 61.318±5.029, 39.818±3.459, 34.715±3.099, 39.386±3.448, and 25.511±2.617, respectively. Conclusions: Midwives working in comprehensive health centers in Qazvin city exhibit strong competency in childbirth counseling, reinforcing their essential role in maternal healthcare.